2007
DOI: 10.1016/j.jconrel.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transferrin iron release increases in vitro drug carrier efficacy

Abstract: Transferrin (Tf) conjugates of CRM107 are currently being tested in clinical trials for treatment of malignant gliomas. However, the rapid cellular recycling of Tf limits its efficiency as a drug carrier. We have developed a mathematical model of the Tf/TfR trafficking cycle and have identified the Tf iron release rate as a previously unreported factor governing the degree of Tf cellular association. The release of iron from Tf is inhibited by replacing the synergistic carbonate anion with oxalate. Trafficking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 32 publications
0
48
0
Order By: Relevance
“…An important property of drug carriers that has particular significance in pharmacy is their ability to increase the solubility of poorly soluble drugs in water and have non-covalent interaction with the drug to facilitate the delivery [14]. We have shown that TCS become completely soluble in water upon complexation with LZ (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An important property of drug carriers that has particular significance in pharmacy is their ability to increase the solubility of poorly soluble drugs in water and have non-covalent interaction with the drug to facilitate the delivery [14]. We have shown that TCS become completely soluble in water upon complexation with LZ (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…It has been shown that the type of interaction between protein and phenolic compounds is an important factor in producing effective delivery system. Specifically, it was demonstrated that weak binding affinity of phenolic drug to the carrier molecule is correlated with the effectiveness of drug delivery [14]. Therefore, the effectiveness of phenolic drug-LZ conjugates may be explored by identifying a phenolic antibiotic for LZ that exhibits a less degree of association.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, transferrin receptor was investigated as a potential tumor-targeting mechanism, in combination with mutant DT, as this receptor is expressed on the surface of many types of cancer, including GBM. 12 A mutant DT fused to a molecule of transferrin administered via CED was initially investigated; however, rapid transferrin cycling within the cell limited the duration of toxin exposure reducing potential therapeutic efficacy, 13 Mutant forms of transferrin fused with DT were then investigated in clinical studies; however, this treatment did not increase overall survival when compared with standard therapy. 14 Currently, DT conjugated with a transferrin receptor antibody administered via CED to patients with GBM is being investigated in clinical trials.…”
Section: Selected Local Therapiesmentioning
confidence: 99%
“…An important property of drug carriers that has particular significance in pharmacy is their ability to increase the solubility of poorly soluble drugs in water and have non-covalent interaction with the drug to facilitate delivery [37]. The insoluble triclosan becomes completely soluble in water on complexation with lysozyme ( Figure 5B), most probably as the phenolic ring is incorporated, non-covalently, into the hydrophobic core underlying the active site cleft of lysozyme, as deduced from fluorescence study.…”
Section: Physicochemical Stability Of Phenolic Drug-lysozymementioning
confidence: 96%
“…Specifically, it has been demonstrated that weak binding affinity of phenolic drug to the carrier molecule is correlated with the effectiveness of drug delivery [37]. Therefore, the effectiveness of phenolic drug-lysozyme conjugates may be explored by identifying a phenolic antibiotic for lysozyme that shows a lesser degree of association.…”
Section: The Rationale Of Lysozyme Molecule As Phenolic Drug Carriermentioning
confidence: 99%